Understanding decentralised governance and making it a viable component of democracy and development in Kerala - Oommen, M.A. (2017)
This article critiques the salience of decentralized governance of Kerala within the conceptual framework of democratic governance. If democracy were to reflect the proverbial definition of government, of the people, by the people, for the people, it must be experienced every day. The social choices of the people must be reflected in the governance of the community. Representative democracy that lays primary focus on balloting is a poor and incomplete version of democracy. People are the means and ends of democracy. For ensuring justice for the disadvantaged and for working towards an inclusive society, local democracy has to play a vital and continuing role. The suggestions for improving the democratic practice in Kerala given in this article will be of use and relevance for other states as well. - Reproduced.
Keywords: Decentralization - India - Kerala; Decentralization